Building Entrepreneurial Skills Program at PKBM Farilla Ilmi Padang - Heru Prasetia; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2023)
This research was motivated by the PKBM Farilla Ilmi institution, Padang City, which has one program, namely Entrepreneurial Skills Education. The entrepreneurial skills education program is intended as initial capital for students, so that their mental preparation and development of mental preparation and entrepreneurship become independent, understand several skill techniques and also the basis of business management to solve economic problems. The implementation of the entrepreneurial skills education program at PKBM Farilla Ilmi, there is one of them is training to make flower pot crafts and paintings from coconut fiber. One of the objectives to be achieved by the entrepreneurship skills education program is increasing business ability to develop and realize the abilities of PKBM students, strengthening the empowerment of PKBM students by increasing knowledge, attitudes and skills, increasing business motivation, creating awareness about the utilization of potential local. This type of research is descriptive with a qualitative approach. Sources of data in this study were the head of PKBM, tutors, and residents studying the entrepreneurial skills education program. Data collection techniques used in this study were interviews, observation and documentation. The analysis technique in this research is data reduction, data presentation, and conclusion drawing. The wetness of the data obtained from this study is triangulation of sources and theories. The results of the research and discussion are 1) Development of entrepreneurial skills education programs; 2) Description of the entrepreneurial skills education program; 3) Evaluation of entrepreneurship skills education program; 4) Lack of entrepreneurial skills education programs; 5) Coconut fiber crafts.